Metastable Ta2N3 with highly tunable electrical conductivity via oxygen incorporation. Issue 6 (1st April 2021) - Jiang, Chang-Ming; Wagner, Laura I.; Horton, Matthew K.; Eichhorn, Johanna; Rieth, Tim; Kunzelmann, Viktoria F.; Kraut, Max; Li, Yanbo; Persson, Kristin A.; Sharp, Ian D.
Abstract : Metastable Ta2 N3 with bixbyite structure is directly deposited by reactive magnetron sputtering. Concerted experimental and computational efforts reveal the crucial role of oxygen impurity in both the synthesis and in tuning the electronic structure. Abstract : The binary Ta–N chemical system includes several compounds with notable prospects in microelectronics, solar energy harvesting, and catalysis. Among these, metallic TaN and semiconducting Ta3 N5 have garnered significant interest, in part due to their synthetic accessibility. However, tantalum sesquinitride (Ta2 N3 ) possesses an intermediate composition and largely unknown physical properties owing to its metastable nature. Herein, Ta2 N3 is directly deposited by reactive magnetron sputtering and its optoelectronic properties are characterized. Combining these results with density functional theory provides insights into the critical role of oxygen in both synthesis and electronic structure. While the inclusion of oxygen in the process gas is critical to Ta2 N3 formation, the resulting oxygen incorporation in structural vacancies drastically modifies the free electron concentration in the as-grown material, thus leading to a semiconducting character with a 1.9 eV bandgap. Reducing the oxygen impurity concentration via post-synthetic ammonia annealing increases the conductivity by seven orders of magnitude and yields the metallic characteristics of a degenerate semiconductor, consistent with theoretical predictions. Thus, this inverse oxygen doping approach – by which the carrier concentration is reduced by the oxygen impurity – offers a unique opportunity to tailor the optoelectronic properties of Ta2 N3 for applications ranging from photochemical energy conversion to advanced photonics.